IMPLEMENTASI PROJECT-BASED LEARNING DALAM DESAIN ARSITEKTUR SATU SEBAGAI UPAYA PENINGKATAN KREATIFITAS MAHASISWA - Ernawati, Ernawati; Yusuf, Frida Maryati (Universitas Negeri Gorontalo, 2025)
Architecture, as a discipline encompassing art, engineering, and spatial design, requires an effective educational approach to develop the creativity of aspiring architects. This study aims to evaluate and implement a Project-Based Learning (PjBL) model to enhance the creativity of students in the Architecture Engineering program in the course of Architectural Design 1, focusing on realizing design and architectural techniques through real projects. The research employs Classroom Action Research (CAR), conducted from June to July 2024, involving four classes of students. Data were collected through pre-tests and post-tests measuring student responses to project-based learning. The findings indicate that students feel more creative when given tasks that engage them directly in the classroom to sharpen their skills and broaden their knowledge. The implementation of the PjBL model proves effective in enhancing students' creative achievements through activities such as creating shape simulations using materials that reflect their creativity and accurately analyzing spaces based on human activities and the facilities available in simple buildings. These findings underscore the importance of integrating the PjBL model into the architecture curriculum to facilitate the development of students' creativity and design skills